Effective and selective recovery of gold and palladium ions from metal wastewater using a sulfothermophilic red alga, Galdieria sulphuraria. (July 2016) - Ju, Xiaohui; Igarashi, Kensuke; Miyashita, Shin-ichi; Mitsuhashi, Hiroaki; Inagaki, Kazumi; Fujii, Shin-ichiro; Sawada, Hitomi; Kuwabara, Tomohiko; Minoda, Ayumi
Highlights: Galdieria sulphuraria cells absorbed precious metals from HCl solution. They selectively recovered Au 3+ and Pd 2+ from aqua regia-based metal wastewater. Au 3+ and Pd 2+ can be eluted from G. sulphuraria as soluble complexes. The selective recovery and elution process can be completed within 1 h. Abstract: The demand for precious metals has increased in recent years. However, low concentrations of precious metals dissolved in wastewater are yet to be recovered because of high operation costs and technical problems. The unicellular red alga, Galdieria sulphuraria, efficiently absorbs precious metals through biosorption. In this study, over 90% of gold and palladium could be selectively recovered from aqua regia-based metal wastewater by using G. sulphuraria . These metals were eluted from the cells into ammonium solutions containing 0.2 M ammonium salts without other contaminating metals. The use of G. sulphuraria is an eco-friendly and cost-effective way of recovering low concentrations of gold and palladium discarded in metal wastewater.